Analysis of the results achieved by the romanian women biathlonists during the senior world championships at the 15 km event - Balint, G.; Puiu, C. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Revitalization of the Romanian competition biathlon can be achieved only by changing some of the organizational-methodical elements included in the complex sports training process. We actually state that the more flexible and moulded (according to the objective competitions) the sports training in biathlon becomes, the greater the chances of achieving maximum results during the competitions are.